HUBUNGAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI DI KPUD KABUPATEN MAMASA - Andriani Andriani; Merianus Merianus (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to determine the relationship of leadership with employee job satisfaction in the Election Commission of Mamasa Regency. This research is an explanatory research with a quantitative approach. Data collection is done through observation, questionnaires, and document review. Data were analyzed using descriptive statistical techniques and inferential statistical techniques. The results showed that leadership was partially positively related to employee job satisfaction. Leadership influences employee job satisfaction with a level of influence of 90%, while 10% is influence by other variables outside the leadership variable.